2022
DOI: 10.1177/13674935221083451
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ knowledge and practices on breastfeeding and complementary feeding in an urban slum area and rural area in Kenya: A cross-sectional interview study

Abstract: Maternal breastfeeding and complementary feeding knowledge is an important determinant of childrens’ long-term health and development. This study aims to account for associations between knowledge and practices in Kenya and report the food consumption of children from birth to 18 months. In 2015 mother–child pairs were recruited from Mother-and-Child Health Centers; 415 in an urban slum in Nairobi and 364 in rural Machakos. Knowledge and practice scores were calculated from questionnaire variables and 24-h foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This difference might be attributed to several factors, including poor knowledge about the importance and benefits of effective breastfeeding, lack of breastfeeding-friendly workplaces, lack of support from family members, and harmful traditional practices. Additionally, limited access to healthcare, including comprehensive breastfeeding education and counseling programs, as well as inadequate postnatal and prenatal care for women living in resettlement areas, may contribute to this disparity ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be attributed to several factors, including poor knowledge about the importance and benefits of effective breastfeeding, lack of breastfeeding-friendly workplaces, lack of support from family members, and harmful traditional practices. Additionally, limited access to healthcare, including comprehensive breastfeeding education and counseling programs, as well as inadequate postnatal and prenatal care for women living in resettlement areas, may contribute to this disparity ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also saw that mothers generally know about feeding recommendations for young children, but caregivers cannot implement such practices due to similar barriers as observed in our study. Similarly, in rural Machakos, close to Nairobi, Uusimäki et al confirmed that complementary feeding knowledge is good among mothers living in informal settlements [41]. In addition, in two neighbouring counties of Siaya, Homa Bay, and Migori, a recent qualitative study with 29 key informants revealed that caregivers are indeed knowledgeable and skilled enough to execute healthy child feeding practices.…”
Section: Stages Of Changementioning
confidence: 93%